Pollination in Plants 2018
DOI: 10.5772/intechopen.75361
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Cocoa Pollination: The Case of Côte d’Ivoire

Abstract: Cocoa (Theobroma cacao L.) is mainly pollinated by ceratopogonid midges (Forcipomyia spp.). However, other insect species will also pollinate cocoa flowers when these midges are scarce. In Côte d'Ivoire, inadequate pest control practices (insecticide spraying, mostly against the mirids Distantiella theobromae and Sahlbergella singularis) and landscape degradation as a result of deforestation and cocoa monoculture, have decreased overall pollinator population levels and, as a result, pollination services to coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 66 publications
0
15
0
9
Order By: Relevance
“…mirids are particularly harmful (and usually lethal) to cocoa cherelles (Anikwe and Otuonye, 2015; Wheeler, 2001), trees where lower cherelle numbers were recorded, were probably more affected by mirids than other trees. It is, however, also possible that differences in cherelle numbers are caused by differences in cocoa genotypes, soil nutrition or pollinator abundance between the studied cocoa farms, which will cause differences in physiological cherelle wilt, a natural fruit thinning mechanism in cocoa (Valle et al, 1990;Claus et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…mirids are particularly harmful (and usually lethal) to cocoa cherelles (Anikwe and Otuonye, 2015; Wheeler, 2001), trees where lower cherelle numbers were recorded, were probably more affected by mirids than other trees. It is, however, also possible that differences in cherelle numbers are caused by differences in cocoa genotypes, soil nutrition or pollinator abundance between the studied cocoa farms, which will cause differences in physiological cherelle wilt, a natural fruit thinning mechanism in cocoa (Valle et al, 1990;Claus et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This factor is influenced by the variation in the richness and abundance of pollinators in the cocoa fields. Thus, pollination is expected to be higher within the shaded cocoa systems compared to the monoculture systems since insect and pollinator biodiversity is higher within agroforestry systems and forest systems [41]. Additionally, a study in Ghana by [42] showed that the cocoa intercrop could enhance cocoa pollination.…”
Section: Pollinationmentioning
confidence: 99%
“…Yield gaps effectively estimate the potential to improve crop yields by optimizing the pollination environment. In Ivory Coast, yield loss in cocoa production was often attributed to disease, pests, and low soil fertility, but there is increasing evidence that inadequate pollination provision of cocoa has also played a significant role (Claus et al 2018). Despite the availability of effective agronomic management practices to increase cocoa production, the benefits gained from pollination services are not commonly considered at the local level (Toledo-Hernández et al 2017).…”
Section: Importance Of Pollination Services and Pollinator Conservation In Ssamentioning
confidence: 99%